2021
DOI: 10.1002/cb.1939
|View full text |Cite
|
Sign up to set email alerts
|

To engage or not engage? The features of video content on YouTube affecting digital consumer engagement

Abstract: Popularity on YouTube is an important metric for influencers and brands. It is linked to video relevance, content, and features that attract audience attention and interest. We present and test a model of YouTube video popularity drivers that trigger several engagement actions (i.e., number of views, likes, dislikes, and comments). These drivers include characteristics—such as language elements, linguistic style, subjectivity, emotion valence, and video category—that influence online video popularity on YouTub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 50 publications
1
38
0
5
Order By: Relevance
“…Therefore, the greater a customer's cognitive, emotional and behavioral investment in a destination brand (e.g., by learning about, discussing, or recommending the brand to others), the higher his/her brand engagement (Kumar & Pansari, 2016 ; So et al, 2021 ). In turn, the individual's engagement has been shown to yield important effects on consumers' (e.g., repurchase) behavior (e.g., Kumar et al, 2019 ; Munaro et al, 2021 ; Naeem & Ozuem, 2021 ).…”
Section: Literature Review and Conceptual Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the greater a customer's cognitive, emotional and behavioral investment in a destination brand (e.g., by learning about, discussing, or recommending the brand to others), the higher his/her brand engagement (Kumar & Pansari, 2016 ; So et al, 2021 ). In turn, the individual's engagement has been shown to yield important effects on consumers' (e.g., repurchase) behavior (e.g., Kumar et al, 2019 ; Munaro et al, 2021 ; Naeem & Ozuem, 2021 ).…”
Section: Literature Review and Conceptual Developmentmentioning
confidence: 99%
“…Customer engagement has been defined as a customer's resource investment in his/her brand interactions (Kumar et al, 2019 ), revealing its inherently interactive nature (Behnam et al, 2021 ; Munaro et al, 2021 ). During the pandemic, customer/brand interactions have been severely impacted (e.g., through lockdowns/social distancing; Aziz & Long, 2021 ), thus impacting customers' brand engagement (vs. pre ‐the pandemic), which―however―remains scant (Hollebeek et al, 2021 ), revealing an important gap.…”
Section: Introductionmentioning
confidence: 99%
“…Literature has discovered that video length is one of the cardinal features with a significant impact on digital consumer engagement [16], defined as the attention span required for media entertainment [17]. Similarly, Jang et al connected duration to narrative engagement [18], a discourse effort that becomes more important with excessive video length.…”
Section: Research Modelmentioning
confidence: 99%
“…Research found further, for example, that "postings during non-business hours also helps to increase the number of views, likes and comments" (Munaro et al, 2021, p. 13). Other identified criteria affecting the success of a video on YouTube seem to be the video-length, language style and emotion (Munaro et al, 2021). In addition, tutorials, interviews with experts and videos with answers to recurring customer questions can generate a proactive exchange.…”
Section: The Youtube Video Platformmentioning
confidence: 99%